A review of executive functioning challenges and strengths in autistic adults. Issue 5 (4th July 2022) - St. John, Tanya; Woods, Sara; Bode, Tammara; Ritter, Cassidy; Estes, Annette
Abstract: Objective: There has been a steady rise in research characterizing executive functioning (EF) impairments in autistic individuals but limited research investigating EF strengths. This review provides a summary of current EF research in autistic adults with a focus on EF challenges and strengths and potential sources of heterogeneity in research findings. New avenues for addressing gaps in our understanding of EF strengths are proposed. Method: A review of the EF literature was conducted. One hundred twenty-four studies of inhibition, working memory, cognitive flexibility, fluency, planning, decision-making, and subjective measures of EF in autistic adults were included. Results: Autistic adults with average intellectual functioning demonstrate difficulties with cognitive flexibility, phonemic fluency, and working memory. Strengths in planning, decision-making, and semantic verbal fluency were evident in some but not all studies. Findings regarding inhibition are inconclusive. Key findings across each EF domain are discussed and sources of potential heterogeneity across studies were evaluated. The type of measure used appears to contribute to heterogeneous findings. Subjective EF measures revealed more consistent findings of deficits in autistic adults than objective EF measures. Conclusions: Research reveals areas of EF weaknesses as well as strengths in autistic adults. Unlike EF challenges, EF strengths are not well understood. Future research identifying EF strengths is needed to improve services and supports for autistic adults. Further investigation of potential factors that interact with or constrain EF such as comorbid disorders, verbal ability, sensory processing, and other factors specific to autism will be critical to move the field forward and increase understanding of how EF is related to everyday functioning in autistic adults.